2013
DOI: 10.1007/s40263-013-0104-8
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Lisdexamfetamine Dimesylate and Atomoxetine in the Treatment of Attention-Deficit/Hyperactivity Disorder: a Head-to-Head, Randomized, Double-Blind, Phase IIIb Study

Abstract: ObjectivesThe aim of this study was to compare the efficacy and safety of the prodrug psychostimulant lisdexamfetamine dimesylate (LDX) and the non-stimulant noradrenergic compound atomoxetine (ATX) in children and adolescents with attention-deficit/hyperactivity disorder (ADHD) who had previously responded inadequately to methylphenidate (MPH).MethodsThis 9-week, head-to-head, randomized, double-blind, active-controlled study (SPD489-317; ClinicalTrials.gov NCT01106430) enrolled patients (aged 6–17 years) wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
75
1
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(91 citation statements)
references
References 37 publications
10
75
1
5
Order By: Relevance
“…Most clinical efficacy studies only report inattention/hyperactivity-impulsivity measures (ADHD IV) (Dittmann et al 2013) and clinical global impression (CGI) (Setyawan et al 2013). These studies do not assess efficacy in improving LTM.…”
Section: Discussionmentioning
confidence: 99%
“…Most clinical efficacy studies only report inattention/hyperactivity-impulsivity measures (ADHD IV) (Dittmann et al 2013) and clinical global impression (CGI) (Setyawan et al 2013). These studies do not assess efficacy in improving LTM.…”
Section: Discussionmentioning
confidence: 99%
“…Reductions in body weight have also been detected in children and adolescents treated with lisdexamfetamine [74] and methylphenidate [21,75,86] in some comparative studies using atomoxetine. In a 9-week randomized, double-blind study, reductions in body weight were greater with lisdexamfetamine (mean [SD] -1.30 kg [1.81]) than with atomoxetine (-0.15 kg [1.43]), and a greater proportion of patients had a C7 % reduction in weight from baseline with lisdexamfetamine (26.8 %; N = 34/127) than with atomoxetine (4.5 %; N = 6/132) [74].…”
Section: Findings In the Predefinedmentioning
confidence: 94%
“…Weight In short-term controlled and open-label studies (B18 weeks), reductions in weight have been reported in children and adolescents during treatment with atomoxetine [18,53,55,62,65,67,74,79,82,89]. However, reductions in body weight are not universally reported: the authors of some short-term studies (B14 weeks) report either no change or a small increase in mean weight [55,69,75,80,81] and/or describe weight changes as not ''clinically significant'', not ''clinically meaningful'', or ''small'' [55,67,79,80,86].…”
Section: Findings In the Predefinedmentioning
confidence: 99%
See 1 more Smart Citation
“…This study was conducted in 267 children and adolescents, comparing LDX (in doses of 30, 50 or 70 mg) and atomoxetine (0.5 to 1.2 mg/kg) over 9 weeks 37 . LDX was associated with a significantly more rapid and robust treatment response than atomoxetine.…”
Section: Efficacymentioning
confidence: 99%